Playing Around With Morality: Introducing the Special Issue on "Morality Play". Issue 4 (June 2019) - Ryan, Malcolm; Formosa, Paul; Tulloch, Rowan
This special issue of Games and Culture focuses on the intersection between video games and ethics. This introduction briefly sets out the key research questions in the research field and identifies trends in the articles included in this special issue.